Daily stress and coping styles in adolescent hopelessness depression: Moderating effects of gender. - Rodríguez-Naranjo, María Carmen; Caño-González, Antonio (Personality and Individual Differences, 2016)
The hopelessness depression (HD) theory assumes a number of contributing factors to the development of hope- lessness expectations and HD symptoms. However, little research has been conducted in order to examine gen- der differences in the relationship of these factors with HD. This study explored the relationship of daily stress and coping styles with HD in adolescents and analysed the moderating effects of gender. Secondary students (N = 480; aged 13–17) completed the Hopelessness Scale, the Hopelessness Depression Symptoms Question- naire, the Problem Questionnaire and the Coping Across Situations Questionnaire. Using hierarchical regression analyses, results showed a moderating effect of gender on the relationship between daily stress and hopelessness expectations, which revealed a significant effect for boys despite the fact that girls experienced more daily stress than boys. Regarding coping styles, results showed that the avoidant coping style predicted HD independently of gender and, interestingly, a moderating effect of gender for the active and internal coping styles. While the active coping style showed a protective effect for HD symptoms in girls, the internal coping style played an analogous role in boys, suggesting that girls would benefit from being more action-prone and boys from being more reflection-prone in order to prevent HD.
Keywords: Adolescentes - Psicología; Depresión mental; Estrés (Psicología); Coping styles; Daily stress; Hopelessness depression; Adolescence; Gender moderation